Combining deep learning and radiomics for automated, objective, comprehensive bone marrow characterization from whole-body MRI: a multicentric feasibility study - Wennmann, Markus; Klein, André; Bauer, Fabian; Chmelik, Jiri; Grözinger, Martin; Uhlenbrock, Charlotte; Lochner, Jakob; Nonnenmacher, Tobias; Rotkopf, Lukas Thomas; Sauer, Sandra; Hielscher, Thomas; Götz, Michael; et al. (Investigative radiology, 2022)
Disseminated bone marrow (BM) involvement is frequent in multiple myeloma (MM). Whole-body magnetic resonance imaging (wb-MRI) enables to evaluate the whole BM. Reading of such whole-body scans is time-consuming, and yet radiologists can transfer only a small fraction of the information of the imaging data set to the report. This limits the influence that imaging can have on clinical decision-making and in research toward precision oncology. The objective of this feasibility study was to implement a concept for automatic, comprehensive characterization of the BM from wb-MRI, by automatic BM segmentation and subsequent radiomics analysis of 30 different BM spaces (BMS).